Art and Museums in the Digital Age: An Overview of the Concepts and Spatial Design - Burkut, Emine Banu; Tekin, Seçkin; Dal, Murat (Art and Design (OJAD), 2025)
Starting in the 20th century, with the acceleration of technological developments, the increasing use of technology, and the change in social structures due to the computer or the internet, there has been a transition to the so-called 'technological age', or 'digital age'. With these technological developments, the products of the 'individual', whose perception has changed, define the past, culture, and future through art in order to exist in the society that surrounds it, to sustain its existence, and to internalize the culture of the society. Digital art is located at the intersection of culture, art, media, contemporary art, digitalization, and technology. Digital art enables both visual thinking and software skills to be learned together. At the same time, the process of creating dynamic images using digital applications requires a multifaceted design phase. Through digital art, the viewer who examines the work of art has become active. Digital art transforms the traditional understanding of art and changes the way artworks are created and experienced. By interacting with the artwork, viewers have become active participants and users of artwork. In the digital age, the exhibition of art on digital platforms enables art to reach wider audiences. This situation has made participants/users eager to visit. In addition, digital museums and digital exhibitions are attracting a lot of attention and their number is increasing every year. Digital art therapy is a rapidly growing practice in recent years. With the opportunities brought by the digital age, digital art brings along a new search for aesthetics and meaning in the art world. In this research, the concept of digital art in the digital age and the works published in this field are examined as an area that has been widely discussed and attracted attention in recent years. This research aims to contribute to the field by focusing on digital art, digital museums and digital exhibitions. In addition, in order to make the existing publications visible, the texts will be visualized to make them more effective for the reader.
Keywords: Digital Age; Digital Art; Digital Museum; Technology; Keyword and Visual Analysis